1962
DOI: 10.1002/j.1551-8833.1962.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimums in Diatomite Filtration

Abstract: This article discusses the different factors of diatomite filtration which may be optimized before the proper body feed, filtration rate, and terminal head loss can be selected. The overall optimum body feed, optimum filtration rate, and optimum terminal head loss combine to produce potable water at the minimum cost per gallon. These optimums are influenced by four cost factors: labor, power, diatomite, and equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…' Previous research has shown that two types of curves develop in constantrate diatomite filtration when plotting head loss against time of filtration or volume of filtrate. ': z, 7 A typical series of such head loss against time curves is shown in Fig. 1.…”
mentioning
confidence: 99%
“…' Previous research has shown that two types of curves develop in constantrate diatomite filtration when plotting head loss against time of filtration or volume of filtrate. ': z, 7 A typical series of such head loss against time curves is shown in Fig. 1.…”
mentioning
confidence: 99%
“…All tests were made with University tap water to which ferrous sulfate was added. The results and conclusions drawn from these tests have been published in several articles (9,10,45).…”
Section: Optimum Design Of Precoat Filtersmentioning
confidence: 99%
“…The amount of precoat filter aid used in lb/month is equal to ; PFA = w(Area)N (45) where N is the number of filter runs per month and is equal to 24 hr/day x 30.4 days/month divided by the filter run length.…”
Section: Filter Aid Costmentioning
confidence: 99%